2018
DOI: 10.1124/dmd.118.081273
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Priority Natural Products for Evaluation as Potential Precipitants of Natural Product–Drug Interactions: A NaPDI Center Recommended Approach

Abstract: Pharmacokinetic interactions between natural products (NPs) and conventional medications (prescription and nonprescription) are a longstanding but understudied problem in contemporary pharmacotherapy. Consequently, there are no established methods for selecting and prioritizing commercially available NPs to evaluate as precipitants of NP-drug interactions (NPDIs). As such, NPDI discovery remains largely a retrospective, bedside-to-bench process. This Recommended Approach, developed by the Center of Excellence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
(22 reference statements)
0
27
0
Order By: Relevance
“…As with drug-drug interactions, common mechanisms underlying natural product-drug interactions include inhibition of drug metabolizing enzymes, particularly the cytochromes P450 (CYPs), by precipitant ("perpetrator") constituents in natural products (Johnson et al, 2018;Paine et al, 2018). Kratom extracts, when tested using recombinant enzymes with fluorometric or luminogenic CYP probe substrates, inhibited CYP2D6, CYP3A, and CYP1A2 activity (IC 50 : 0.64-3.6 µg/mL, 0.78-140 μg/mL, and 39 μg/mL, respectively) (Kong et al, 2011;Hanapi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As with drug-drug interactions, common mechanisms underlying natural product-drug interactions include inhibition of drug metabolizing enzymes, particularly the cytochromes P450 (CYPs), by precipitant ("perpetrator") constituents in natural products (Johnson et al, 2018;Paine et al, 2018). Kratom extracts, when tested using recombinant enzymes with fluorometric or luminogenic CYP probe substrates, inhibited CYP2D6, CYP3A, and CYP1A2 activity (IC 50 : 0.64-3.6 µg/mL, 0.78-140 μg/mL, and 39 μg/mL, respectively) (Kong et al, 2011;Hanapi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The first charge of the NaPDI Center was to select and prioritize the NPs to be studied as potential precipitants of NPDIs. A systematic method was developed to identify four priority NPs that will serve as exemplars for the Recommended Approaches (Johnson et al, 2018). Beginning with a list of 47 commonly used NPs, these four NPs were selected based on existing in vitro and clinical data suggesting the potential to precipitate a NPDI.…”
Section: Recommended Approachesmentioning
confidence: 99%
“…It provides a user-friendly interface that enables users with limited informatics skills to effectively explore relevant data (Li, 2015). As of March 2020, coverage of the repository is limited to four carefully selected high-priority NPs based on a systematic method for the purpose of demonstrating the Recommended Approaches (Johnson et al, 2018): cannabis (Cannabis sativa), goldenseal (Hydrastis canadensis), green tea (Camellia sinensis), and kratom (Mitragyna speciosa). A prior Recommended Approach (Johnson et al, 2018) reported the inclusion of licorice (Glycyrrhiza spp.).…”
Section: Introductionmentioning
confidence: 99%
“…One objective of the NaPDI Center is to develop and apply a set of Recommended Approaches to determine the clinical relevance of pharmacokinetic NPDIs ( Johnson et al, 2018 ; Paine et al, 2018 ; Kellogg et al, 2019 ). A key deliverable of the Center is the development of an online repository for data generated by the NaPDI Center ( repo.napdi.org ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation